Novel hepaci- and pegi-like viruses in native Australian wildlife and non-human primates. Issue 2 (20th August 2020) - Porter, Ashleigh F; Pettersson, John H -O; Chang, Wei-Shan; Harvey, Erin; Rose, Karrie; Shi, Mang; Eden, John-Sebastian; Buchmann, Jan; Moritz, Craig; Holmes, Edward C
Abstract: The Flaviviridae family of positive-sense RNA viruses contains important pathogens of humans and other animals, including Zika virus, dengue virus, and hepatitis C virus. The Flaviviridae are currently divided into four genera— Hepacivirus, Pegivirus, Pestivirus, and Flavivirus —each with a diverse host range. Members of the genus Hepacivirus are associated with an array of animal species, including humans, non-human primates, other mammalian species, as well as birds and fish, while the closely related pegiviruses have been identified in a variety of mammalian taxa, also including humans. Using a combination of total RNA and whole-genome sequencing we identified four novel hepaci-like viruses and one novel variant of a known hepacivirus in five species of Australian wildlife. The hosts infected comprised native Australian marsupials and birds, as well as a native gecko ( Gehyra lauta ). From these data we identified a distinct marsupial clade of hepaci-like viruses that also included an engorged Ixodes holocyclus tick collected while feeding on Australian long-nosed bandicoots ( Perameles nasuta ). Distinct lineages of hepaci-like viruses associated with geckos and birds were also identified. By mining the SRA database we similarly identified three new hepaci-like viruses from avian and primate hosts, as well as two novel pegi-like viruses associated with primates. The phylogenetic history of the hepaci- and pegi-like viruses as a whole, combined with co-phylogenetic analysis, provided support for virus-host co-divergence over the course of vertebrate evolution, although with frequent cross-species virus transmission. Overall, our work highlights the diversity of the Hepacivirus and Pegivirus genera as well as the uncertain phylogenetic distinction between.